The crime victim in bail proceedings: the uncertain balance of a new but still unmeditated protagonism - Lina Caraceni (Revista Brasileira de Direito Processual Penal)
A renewed attention on the crime victim’s issues has led to strengthen her/his role in criminal proceedings in two dimensions: as holder of the right to be protected in the process (repeated victimization) and from the process (secondary victimization) and as an active subject, capable of exercising rights and faculties to protect her/his psycho-physical integrity. The protection system was built on vulnerable victims, taking into account the indications of European Union law. The main reform has seen the introduction of pro victima measures in the pre-trial stage (artt. 282-bis and 282-ter c.p.p.) and the victim right to information on the evolution of the custody status of the accused (artt. 90-ter, 282-quater and 299 paragraph 2-bis c.p.p.) which is associated with a right to participate in the procedures for the enforcement and disposal of the measures (artt. 299 paragraph 3 and 4-bis c.p.p.). The analysis will focus on this second aspect, highlighting that the procedural law gives a new key role to the victim. Unfortunately, the hoped-for results have not been achieved: unclear legal language and lack of coordination between the various reforms have compromised the goal of protecting the victim and have introduced the risk that guarantees provided to the accused in the decision-making procedures about her/his personal liberty will be neutralized.